Room Temperature Detection of Hydrogen Peroxide Vapor by Fe2O3:ZnO Nanograins - Aleksanyan, Mikayel; Sayunts, Artak; Shahkhatuni, Gevorg; Simonyan, Zarine; Kasparyan, Hayk; Kopecký, Dušan (Nanomaterials (Basel, Switzerland), 2022)
In this report, a Fe2O3:ZnO sputtering target and a nanograins-based sensor were developed for the room temperature (RT) detection of hydrogen peroxide vapor (HPV) using the solid-state reaction method and the radio frequency (RF) magnetron sputtering technique, respectively. The characterization of the synthesized sputtering target and the obtained nanostructured film was carried out by scanning electron microscopy (SEM), transmission electron microscopy (TEM), and energy-dispersive X-ray (EDX) analyses. The SEM and TEM images of the film revealed its homogeneous granular structure, with a grain size of 10-30 nm and an interplanar spacing of Fe2O3 and ZnO, respectively. EDX spectroscopy presented the real concentrations of Zn in the target material and in the film (21.2 wt.% and 19.4 wt.%, respectively), with a uniform distribution of O, Al, Zn, and Fe elements in the e-mapped images of the Fe2O3:ZnO film. The gas sensing behavior was investigated in the temperature range of 25-250 °C with regards to the 1.5-56 ppm HPV concentrations, with and without ultraviolet (UV) irradiation. The presence of UV light on the Fe2O3:ZnO surface at RT reduced a low detection limit from 3 ppm to 1.5 ppm, which corresponded to a response value of 12, with the sensor's response and recovery times of 91 s and 482 s, respectively. The obtained promising results are attributed to the improved characteristics of the Fe2O3:ZnO composite material, which will enable its use in multifunctional sensor systems and medical diagnostic devices.
Keywords: gas sensor; iron oxide; magnetron sputtering; zinc oxide; hydrogen peroxide vapor; nanograins